Co-occurrence of shedding Herpes Simplex Virus type-2 (HSV-2), Human Papilloma Virus (HPV) and Human Immunodeficiency Virus 1 (HIV-1) in the female genital tract among HIV-infected women - Hu, Nai-Chung (Department of Public Health and Family Medicine, 2020)
Introduction: Human Immunodeficiency Virus remains as one of the largest pandemics in the world, with the prevalence of more than 70% of HIV-infected individual reside in Sub-Saharan Africa. Moreover, other sexually transmitted viral infection such as Human Papillomavirus and Herpes Simplex Virus also show a high prevalence in Sub-Saharan Africa. Recent studies show the presence of other viral STI in the genital region may have increased HIV shedding in the genital region. However, it not clearly known if the presence of ART or HIV may affect the shedding of other viral STI in the genital region and if the combination of other viral STI treatment and ART is necessary to treat an individual with multiple STI infection. Methods: This is a secondary data analysis study, based on analysing the data collected from a single-site, double-blinded randomized control study (2-IUD study). The research site was the Gugulethu Community Health Centre, Cape Town, South Africa and samples were collected between 2014 and 2018. Analysis was conducted on genital tract specimens of study participants obtained via the Menstrual Cup (MC) and Endocervical Swabs (ECS), collected at baseline, 3 and 6 months’ follow up visit from randomly selected 52 ART-Naïve participants and 56 age-matched women from the ART-Using group of the primary study. Logistic regression models were constructed to measure the associations between possible risk factors and viral STIs. Results are presented as odds ratios (OR) with 95% confidence intervals (CI). Results: ART-Naïve women had higher rates of HIV shedding in the genital tract at each visit. However, more than half of women using ART, most of them virally suppressed, had detectable genital HIV at one or more visits. Most of the participants showed pre-exposure to HSV-2, but shedding of HSV-2 was substantially less common. HPV was detected in 72% of the participants, with no significant difference by ART status. Overall, 70.3% of samples had at least one viral pathogen detected - 60.4% among ART-Using women compared to 82.8% in ART-Naïve women (P<0.001). Compared to ART-Naïve women, ART-Using women were significantly less likely to have co-occurrence of viral shedding overall. However, ART-Using women with higher VL had levels of viral co-occurrence similar to those of ART-Naïve women. Conclusion: Our analysis demonstrated that the ART-Using women were less likely to shed HIV, HSV-2, HPV and viral STI co-infection in the genital tract compared to ART-Naïve women. This may be be driven by plasma VL levels where ART-Using women with lower VL are less likely to shed these viruses compared to women with elevated VL, including those not on ART.